Analisis Pencemaran Lingkungan pada Sungai Ciujung Serang Banten Berdasarkan Undang-Undang Nomor 18 Tahun 2008 - Mabsuti Mabsuti; Aris Saiful Putra; Ida Jubaedah; Putri Putri (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Waste is a global issue. Increased waste can cause problems forrthe environment. The main cause of the increase in waste is the household sector. The problem of research into the causes off water pollution in the Ciujung Serang Banten river. This research aims to find out the causes of water pollution in the Ciujung Serang Banten river. This research uses a descriptive analytical approach to describe statutory regulations. The results obtained are not entirely determined by three variables, namely quality, benefits and obligations. Contamination caused by waste resultss in a decrease in water qualityy. Research results can provide information as a basis for consideration, support and ideas for the community to improve environmental sustainability.